Determination of PAHs content in hair samples of smokers and non-smokers using gas chromatography in hyphenation with mass spectrometry - Vi, Phung Thi; Ngoc, Nguyen Thuy; Kim, Truong Thi; Quynh, Nguyen Thi; Anh, Duong Hong; Viet, Pham Hung (VNU Journal of Science: Natural Sciences and Technology, 2019)
PAHs are known as toxic, persistent organic pollutants produced by incomplete combustion of organic materials including smoking. To assess the exposure of PAHs through smoking habits, 16 PAHs in hair samples of 32 smokers and 20 non-smokers were analyzed using gas chromatography in hyphenation with mass spectrometry. The results showed that total content of PAHs in hair samples of smokers ranged from 46.8 ng/g to 1,257 ng/g (mean: 388.3 ng/g) and that of non-smokers ranged from 65.3 ng/g to 910.8 ng/g (mean: 266.1 ng/g). Application of the Student statistical method indicated that the dataset of PAHs in hair samples between two subject groups were significantly different. Phenanthrene, pyrene, fluoranthene were the most dominant PAHs in hair samples of both smokers and non-smokers. The mean content of total toxicity equivalent of 16 PAHs compared to benzo (a) pyrene in hair samples of smokers and non-smokers were 13.32 ng/g and 11.29 ng/g, respectively. Some considerable values of PAHs including PAH4, PAH8 and BaPeq were higher than other similar studies in the world except one study in Japan. The analysis of PAHs in a new biomarker such as hair samples is a potential research trend to assess the exposure of PAHs in the human body. Keywords: PAHs, hair sample, smoker, non-smoker. PAHs are known as toxic, persistent organic pollutants produced by incomplete combustion of organic materials including smoking. To assess the exposure of PAHs through smoking habits, 16 PAHs in hair samples of 32 smokers and 20 non-smokers were analyzed using gas chromatography in hyphenation with mass spectrometry. The results showed that total content of PAHs in hair samples of smokers ranged from 46.8 ng/g to 1,257 ng/g (mean: 388.3 ng/g) and that of non-smokers ranged from 65.3 ng/g to 910.8 ng/g (mean: 266.1 ng/g). Application of the Student statistical method indicated that the dataset of PAHs in hair samples between two subject groups were significantly different. Phenanthrene, pyrene, fluoranthene were the most dominant PAHs in hair samples of both smokers and non-smokers. The mean content of total toxicity equivalent of 16 PAHs compared to benzo (a) pyrene in hair samples of smokers and non-smokers were 13.32 ng/g and 11.29 ng/g, respectively. Some considerable values of PAHs including PAH4, PAH8 and BaPeq were higher than other similar studies in the world except one study in Japan. The analysis of PAHs in a new biomarker such as hair samples is a potential research trend to assess the exposure of PAHs in the human body. Keywords: PAHs, hair sample, smoker, non-smoker. References